Aspectos de Qualidade, Atividade Antioxidante e Antimicrobiana de Méis Monoflorais Produzidos por Melipona ssp. no Semiárido Brasileiro - Sousa, Janaína Maria Batista de (2015)
Monofloral honeys produced by Melipona ssp have aspects of physical and chemical quality, sensory and specific bioactive, however, still little studied. The aim of the present study was to characterize the physico-chemical (moisture, protein, proline, hydroxymethyl-furfural, color, electrical conductivity, pH, free acidity, and sugar profile) and sensory aspects (color, viscosity and flavor) of monofloral honeys from Ziziphus joazeiro Mart. (juazeiro), Mimosa quadrivalvis L. (malícia), Croton heliotropiifolius Kunth (velame branco) and Mimosa arenosa willd Poir (jurema branca) produced by Melipona subnitida D. (jandaíra) and M. scutellaris L. (uruçu) in the Brazilian semiarid region. The antioxidant potential (DPPH, ABTS and ORAC) and the antibacterial activity, as well as the polyphenolics profile of each honey were also assessed. The floral source influenced (p ≤ 0.05) the color, acidity, sugar profile, ash and proline content in the honeys. No differences (p ≥ 0.05) were perceived for honeys from the same floral source produced by different bee species. Principal component analysis revealed that most of the variability was defined by the water content, total acidity, glucose, sucrose and color, as well as by acid taste, acid flavor, honey flavor and sweet taste. Juazeiro and velame branco honeys showed the greatest antioxidant activity and scavenging ability in assays with DPPH and ABTS•+ radicals, respectively, while honeys from malícia presented the strongest (p ≤ 0.05) antiperoxyl radical activity in ORAC assay. Juazeiro honeys presented the highest quantities of phenolic acids, particularly of trans-cinnamic, p-coumaric, ellagic, and ferulic acids, and of the flavonioids cathecin, rutin, hesperetin and chrysin, when compared with the other honeys produced by the same bee specie. malícia honeys presented the highest total flavonoids content (TFC) than honeys from velame branco and jurema branca, with the greatest quantities of myricetin, quercetin and kaempterol amongst the honeys studied. The different meliponini honeys presented different antimicrobial effects against the bacterial strains tested, as measured by their minimum inhibitory concentrations (MICs). However, the lowest MICs were found for honeys that presented the highest TPC. The results showed the impact of the botanical source on the physico-chemical and sensory aspects, as well as on polyphenolic profile, antioxidant and antimicrobial of monofloral honey produced by bees Melipona subnitida Duke and Melipona scutellaris L. in the Brazilian semiarid region.